Benchmarking labour market performance and labour market policies: Theoretical foundations and applications - Holger Schütz; Stefan Speckesser; Günther Schmid (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1998)
Over the last few years, benchmarking advanced to a key word in organisational development and change management. Originally, benchmarking was a tool in business studies summarising the process of comparing your own with a similar organisational unit (mostly the competitor) in order to improve the competitive position. Benchmarking must be distinguished from purely analytical methods of comparison: First, performance indicators must be developed which differ from traditional design. Secondly, an organisational unit must be found which can be classified as the best performer concerning the chosen indicators. The comparison then aims at finding options for the improvement of your own organisational unit in different hierarchical levels with the objective to progress in the position of the best performer. – – Benchmarking avancierte in den vergangenen Jahren zu einem Schlüsselbegriff in der Organisationsentwicklung und im Management. Es benennt in seiner disziplinären Heimat, der Betriebswirtschaftslehre, den Vergleich der eigenen mit einer anderen Organisationseinheit zum Ziel der Verbesserung der eigenen Wettbewerbsposition. Benchmarking unterschiedet sich daher von rein analytischen Vergleichen auf zwei Arten: Erstens werden zunächst Leistungsindikatoren entwickelt, die sich von traditionellen Qualitätsindikatoren unterscheiden. Zweitens wird eine vergleichbare Organisationseinheit gewählt, die bezüglich der gewählten Indikatoren als bestpraktizierende eingestuft wird. Der Vergleich, der über verschiedene Hierarchieebenen verfolgt wird, soll den Raum für Verbesserungen der eigenen Organisationseinheit aufzeigen, um selbst in die Position des Bestpraktizierenden aufzurücken.
Keywords: 330